Aerosol transmission for SARS‐CoV‐2 in the dental practice. A review by SIdP Covid‐19 task‐force. (8th November 2020) - Clementini, Marco; Raspini, Mario; Barbato, Luigi; Bernardelli, Francesco; Braga, Giovanni; Di Gioia, Claudio; Littarru, Cristiano; Oreglia, Francesco; Brambilla, Eugenio; Iavicoli, Ivo; Pinchi, Vilma; Landi, Luca; et al.
Abstract: Current evidence suggests that SARS‐CoV‐2, the virus that causes COVID‐19, is predominantly spread from person to person. Aim of this narrative review is to explore transmission modality of SARS‐CoV‐2 to provide appropriate advice to stakeholders, in order to support the implementation of effective public health measures and protect healthcare workers that primary face the disease. "In vivo" and "in vitro" studies from laboratories and hospitals confirmed the presence of surface contamination and provided insight of SARS‐CoV‐2 detection in the air, particularly in indoor settings with poor ventilation where aerosol‐generating procedures were performed. Measures for aerosol reduction, in conjunction with other effective infection control strategies, are needed to prevent the spread of SARS‐CoV‐2 in dental setting.